1996
DOI: 10.1007/bf01411287
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum cytokine concentrations after neurosurgical procedures

Abstract: Cytokine responses to surgical trauma have been studied in 70 patients undergoing various neurosurgical procedures. Serum concentrations of interleukin-1 beta (IL-1 beta), interleukin-6 (IL-6), interleukin-8, (IL-8), tumour necrosis factor-alpha (TNF-alpha), and interferon-gamma (IFN-gamma) were measured before and after surgery using enzyme-linked immunosorbent assays. The serum concentrations of IL-1 beta, IL-8, TNF-alpha, and IFN-gamma did not change significantly following neurosurgical operations. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
(16 reference statements)
1
13
0
1
Order By: Relevance
“…In neutrophils, activation of p38MAPK stimulated by IL-1 is followed by increased expression of CD11b ( 2 integrin) and CD15 (P-selectin ligand) that directly enhances ROS production [39]. Hemorrhagic and ischemic stroke may both result in the increase of cytokines concentration in the peripheral vessels [43,44], but there are also papers not confirming this effect [45,46]. Ferrarese, however, showed stimulation of peripheral leukocytes, manifesting by increase in cytokines release in culture, without an increase of their concentration in the plasma [47].…”
Section: Discussionmentioning
confidence: 96%
“…In neutrophils, activation of p38MAPK stimulated by IL-1 is followed by increased expression of CD11b ( 2 integrin) and CD15 (P-selectin ligand) that directly enhances ROS production [39]. Hemorrhagic and ischemic stroke may both result in the increase of cytokines concentration in the peripheral vessels [43,44], but there are also papers not confirming this effect [45,46]. Ferrarese, however, showed stimulation of peripheral leukocytes, manifesting by increase in cytokines release in culture, without an increase of their concentration in the plasma [47].…”
Section: Discussionmentioning
confidence: 96%
“…Several cells secrete multiple posttranslationally modified forms of IL-6: keratinocytes (43), skeletal muscle cells (44), endothelial cells (45), neurons, microglia, and astrocytes (13)(14)(15). Elevated levels of IL-6 or a defined IL-6 promoter polymorphism are observed in human body fluids during acute and chronic infections (16,20), Kaposi's sarcoma (46,47) and other neoplasia (48 -50), autoimmune diseases (24,(27)(28)(29)(30)(31), endometriosis (51), after third-degree burns (22,43), strenuous exercise (IL-6 concentration increases as much as 100-fold after a marathon) (44) major surgery (17)(18)(19), and ABI (1-7).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic IL-6 is elevated 4 hrs after neurosurgical procedures (18,19) and in children with ABI (1). In a previous study, elevated IL-6 was found in adults with brain death diagnosis (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein expression is similarly increased within 1-5 h of injury, peaking by 3-8 h [19,22,24,[26][27][28][29]. In the clinical setting elevated levels of blood or CSF TNF [30][31][32][33][34][35], IL-1 [34][35][36] and IL-6 [32][33][34][37][38][39][40][41][42][43][44] have been reported in patients following both TBI and nontrauma associated craniotomy.…”
Section: Leucocyte Recruitment Following Traumatic Brain Injurymentioning
confidence: 98%